Identification of changes in the serum proteome of spontaneously hypertensive rats (SHR) following administration of aqueous extracts from ficus deltoidea / Nur Atiqah Haizum Abdullah - Nur Atiqah Haizum, Abdullah (2012)
Ficus deltoidea or better known as Mas Cotek is an herbaceous plant found around the coast of Peninsular Malaysia especially in Terengganu and Kelantan. This plant is believed to have the capability in helping treat or controlling diseases including hypertension. Hypertension is a major disease that affects by many people all over the world. It is one of the main diseases that contribute to high rate of mortality. Even though modern medicine have been used to treat hypertension, some people still believe that traditional medicinal practices such as taking natural products along with healthy lifestyle will significantly improve hypertension. In this study, the capability of F. Deltoidea aqueous extracts in controlling hypertension were evaluated in vitro; using Angiotensin Converting Enzyme (ACE) inhibitory activity assay and through an in vivo study; by looking at the alteration of serum protein profiles in spontaneously hypertensive rats (SHR). Different parts of the plants obtained from two F.deltoidea varieties were used: fruits from the small-leaf variety (SF) and leaves from the big-leaf variety (BL). Changes in serum protein profiles were studied using proteomics techniques involving Sodium Dodecyl Sulphate- Polyacrylamide Gel Electrophoresis (SDS-PAGE), two-dimensional gel electrophoresis (2-DE), Matrix-assisted Laser Desorption / Ionization-Time of Flight / Time of Flight mass spectrometry (MALDI-TOF/TOF) and Surface-Enhanced Laser Desorption / Ionization-Time of Flight mass spectrometry (SELDI-TOF).